RECEPTOR TRPC5 COMO POTENCIAL ALVO FARMACOLÓGICO NO TRATAMENTO DA SÍNDROME METABÓLICA - ARAÚJO, Mizael Calácio (2023)
Sugar-induced metabolic imbalances are a major health problem, as excessive consumption of saccharides has been linked to higher rates of obesity globally. Sucrose, a disaccharide composed of 50% glucose and 50% fructose, is commonly used in the food industry and found in a variety of fast foods, restaurants and processed foods. Added to this, excessive sucrose intake can modulate several cells, pro-inflammatory cytokines and receptors such as the transient receptor potential channels, a family of receptors permeable to Ca+2 involved in processes such as inflammation, pain, depression and energy expenditure. However, the relevance of some receptors of this family such as TRPC4 and TRPC5 for MS and/or its comorbidities remains unclear. The present work evaluated the effect of the TRPC4/TRPC5 blocker (ML204) on metabolic imbalances triggered by early exposure to a diet enriched with sucrose (25%) in mice. For this, 21-day-old C57BL/6 mice (after weaning) were divided into 2 groups, one fed a normal diet (Nuvital®, n = 22) and the other fed a high-sucrose diet (25% Sucrose, n = 22) for 20 weeks. Still, in the 20th week they were treated with ML204 (2mg/kg/day S.C for 1 week) or 3% DMSO in saline (10 ml/kg/day S.C for 1 week) used as control. Animals fed a diet rich in sucrose (HS) showed hyperglycemia, dyslipidemia and increased body mass index. They exhibited accumulation of mesenteric adipose tissue with adipose cells of greater diameter and hepatic steatosis compared to those fed a normal diet. HS mice also exhibited increased levels of adipose, hepatic, and pancreatic TNFα and VEGF. The use of ML204 exacerbated hyperglycemia, dyslipidemia, adipose tissue deposition, hepatic steatosis and adipose tissue and hepatic TNFα in mice fed HS. Normal mice treated with the blocker showed greater hepatic steatosis and number/diameter of adipose tissue cells than those that received the vehicle, but did not show significant changes in tissue inflammation, glucose and lipid levels. The results indicate that TRPC4/TRPC5 complexes protect against metabolic imbalances caused by HS ingestion, and may function as possible therapeutic targets in metabolic disorders.